Rapid self-repairing antibacterial compression garbage truck metal plate coating and preparation method thereof

By applying a coating containing modified phenolic epoxy resin, modified carboxymethyl chitosan and modified self-healing microcapsules on the metal plate of the compressed garbage truck, the problems of insufficient durability and antibacterial properties of the existing coating are solved, and better metal plate protection and environmental cleaning are achieved.

CN119912860AInactive Publication Date: 2025-05-02HUBEI KAILI SPECIAL VEHICLE CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510376511.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-05-02
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing metal plate coating of compressed garbage trucks has poor durability and insufficient antibacterial properties in harsh environments, making it difficult to effectively protect metal plates, resulting in increased corrosion and environmental pollution.

Method used

A quick self-healing antibacterial compression garbage truck metal plate coating is used, and the base coat contains modified phenolic epoxy resin, polyamide curing agent, modified carboxymethyl chitosan and zinc phosphate. The top coat contains styrene-acrylate emulsion, modified lignin, glycol butyl ether and improved self-healing microcapsules to enhance the self-healing and antibacterial properties of the coating.

Benefits of technology

It significantly improves the durability and antibacterial properties of the coating, enhances the protection of metal plates, extends the service life of the coating, and effectively inhibits the growth of bacteria in garbage, and reduces environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912860A_ABST
    Figure CN119912860A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of coating compositions, in particular to a rapid self-repairing antibacterial compression garbage truck metal plate coating and a preparation method thereof. The defects that an existing metal plate coating of the compression garbage truck is poor in durability and antibacterial property are overcome. The metal plate coating is obtained by preparing a bottom coating and a top coating and coating the surface of a metal plate with the bottom coating and the top coating, wherein the bottom coating is prepared from the following raw materials: modified novolac epoxy resin, a polyamide curing agent, modified carboxymethyl chitosan, zinc phosphate and nano silicon dioxide; the surface coating comprises the following components: styrene-acrylate emulsion, modified lignin, ethylene glycol butyl ether, improved self-repairing microcapsules and a polyacrylic acid dispersing agent; by adding the improved self-repairing microcapsules, the self-repairing performance of the coating is enhanced, so that the durability of the coating is enhanced; and by adding modified carboxymethyl chitosan, modified lignin and improved self-repairing microcapsules, the antibacterial property of the coating is also guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coating compositions, in particular to a rapid self-repairing antibacterial compressed garbage truck metal plate coating and a preparation method thereof. Background Art

[0002] In the automotive field, coatings are widely used in the outer metal layer of automobiles, playing an important role in improving the visual effect of the automobile's appearance, and playing a key role in protecting the metal from erosion by external factors. Automotive coatings can provide a variety of properties for the outer metal layer of automobiles. In terms of self-repairing performance, some coatings that use microcapsule-type or intrinsic self-repairing technology can automatically repair damage by releasing repair agents through microcapsule rupture or reorganizing the chemical bonds of the material itself when the coating is slightly scratched or cracked, thereby maintaining the integrity of the coating and extending the service life of the car. In terms of antibacterial properties, coatings with antibacterial agents such as silver ions can effectively inhibit the growth of bacteria and play a positive role in keeping the interior environment of the car clean and hygienic. In terms of corrosion resistance, the protective film formed by the coating can resist common corrosive media such as rain, acidic gases in the air, and salt to prevent metal from rusting. In terms of wear resistance, it can withstand friction during daily use and maintain the smoothness of the car's appearance.

[0003] The external environment faced by compressed garbage trucks is harsh. Garbage contains a large number of bacteria such as Escherichia coli and Staphylococcus aureus, which not only emit unpleasant odors, but may also pose a threat to human health. At the same time, there are acidic food residues, alkaline detergent residues and various corrosive chemicals in the garbage, which continue to corrode the metal plates of garbage trucks. In this environment, existing coatings have exposed obvious deficiencies in the application of metal plates in compressed garbage trucks. In terms of durability, due to long-term impact, friction and harsh environment of garbage, the coating is prone to peeling and wear, making it difficult to provide effective protection for the metal plates for a long time. In terms of antibacterial properties, existing coatings cannot effectively inhibit the growth of a large number of bacteria in the garbage, causing garbage trucks to become places for bacterial breeding, further accelerating the corrosion of metal plates and exacerbating environmental pollution.

[0004] Therefore, a rapid self-repairing antibacterial compressed garbage truck metal plate coating and its preparation method are proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a rapid self-repairing antibacterial compressed garbage truck metal plate coating and a preparation method thereof. The present invention relates to the technical field of coating compositions, and specifically to a rapid self-repairing antibacterial compressed garbage truck metal plate coating and a preparation method thereof. The present invention overcomes the shortcomings of poor durability and poor antibacterial properties of existing compressed garbage truck metal plate coatings. The present invention obtains a metal plate coating by preparing a primer coating and a topcoat coating and applying them on the surface of a metal plate. The raw materials of the primer coating include: modified phenolic epoxy resin, polyamide curing agent, modified carboxymethyl chitosan, zinc phosphate, and nano-silicon dioxide; the topcoat components include: styrene-acrylate emulsion, modified lignin, ethylene glycol butyl ether, improved self-repairing microcapsules, and polyacrylic acid dispersants; the self-repairing properties of the coating are enhanced by adding improved self-repairing microcapsules, thereby enhancing the durability of the coating; the antibacterial properties of the coating are also guaranteed by adding modified carboxymethyl chitosan, modified lignin and improved self-repairing microcapsules.

[0006] To achieve the above object, the present invention provides the following technical solutions: On the one hand, the present invention provides a rapid self-repairing antibacterial compressed garbage truck metal plate coating, including a primer and a topcoat, wherein the primer components include: 45-50 parts of modified phenolic epoxy resin, 20-25 parts of polyamide curing agent, 10-15 parts of modified carboxymethyl chitosan, 6-8 parts of zinc phosphate, and 1-2 parts of nano-silicon dioxide; The top coating components include: 90-100 parts of styrene-acrylate emulsion, 10-15 parts of modified lignin, 2-3 parts of ethylene glycol butyl ether, 10-15 parts of improved self-repairing microcapsules, and 1-2 parts of polyacrylic acid dispersant.

[0007] Preferably, the raw materials for preparing the improved self-healing microcapsules include: 20-25 parts of 2-naphthalene disulfide, 6-8 parts of modified benzalkonium chloride, 100 parts of polyvinyl alcohol, 5 parts of toluene diisocyanate, and 1.50 parts of ethylenediamine; wherein the molecular weight of the polyvinyl alcohol is 88,000.

[0008] Preferably, the raw materials for preparing the modified lignin include: 100 parts of lignin, 30 parts of succinic anhydride, 500 parts of N,N-dimethylformamide, 2 parts of triethylamine, 8-10 parts of silver nitrate, and 20 parts of ascorbic acid; the particle size of the lignin is 200 mesh, and the lignin is an organic solvent type lignin.

[0009] Preferably, the modified phenolic epoxy resin raw material includes: 100 parts of bisphenol A phenolic epoxy resin and 15-20 parts of monobutyl phosphate.

[0010] Preferably, the modified carboxymethyl chitosan raw material includes: 100 parts of carboxymethyl chitosan and 2,3-epoxypropyltrimethylammonium chloride.

[0011] On the other hand, the present invention provides a method for preparing a fast self-repairing antibacterial compressed garbage truck metal plate coating: an interface treatment agent is applied to a metal plate, and the plate is naturally dried at room temperature for 30 minutes to obtain a pretreated metal plate; a primer coating is sprayed on the surface of the pretreated metal plate, and the plate is cured at 25°C for 24 hours to obtain a primer coating metal plate; an interface treatment agent is applied to the primer coating metal plate, and the plate is naturally dried at room temperature for 30 minutes to obtain a pretreated primer coating metal plate; a top coating coating is sprayed on the surface of the pretreated primer coating metal plate, and the plate is cured at 65°C for 1.5 hours to obtain a fast self-repairing antibacterial compressed garbage truck metal plate coating; the interface treatment agent is prepared by dissolving 5 parts of KH-550 in 95 parts of anhydrous ethanol, by weight.

[0012] Preferably, the preparation method of the primer coating is: weigh 45-50 parts of modified phenolic epoxy resin, 20-25 parts of polyamide curing agent, 10-15 parts of modified carboxymethyl chitosan, 6-8 parts of zinc phosphate and 1-2 parts of nano-silicon dioxide, disperse and mix at a speed of 1500rpm for 30min, add xylene to adjust the viscosity, and obtain the primer coating.

[0013] Preferably, the preparation method of the modified phenolic epoxy resin is as follows: in a three-necked flask, 100 parts of bisphenol A phenolic epoxy resin and 15-20 parts of monobutyl phosphate are added, 50 parts of ethyl acetate are added as a solvent, and then 0.3 parts of triethylamine are added, and the reaction is stirred at a constant temperature of 200 rpm and 90° C. for 2-3 hours, and then the reaction system is cooled to room temperature; 2 parts of activated carbon are added to the reaction system, and the reaction is stirred at room temperature for 30 minutes for adsorption and decolorization, and then filtered to obtain a filtrate; and finally the filtrate is vacuum distilled to obtain the modified phenolic epoxy resin.

[0014] Preferably, the preparation method of modified carboxymethyl chitosan is: under stirring, 100 parts of carboxymethyl chitosan powder are added to 400 parts of sodium hydroxide ethanol solution with a mass fraction of 0.125%, and stirred for 30 minutes to prepare a carboxymethyl chitosan dispersion; then 20-25 parts of 2,3-epoxypropyltrimethylammonium chloride solution with a mass concentration of 50% are added to the carboxymethyl chitosan dispersion, and stirred in a water bath at 60°C for 4-6 hours; after the reaction is completed, centrifuge and wash the precipitate 3 times; finally, dry the precipitate in a vacuum drying oven to obtain modified carboxymethyl chitosan.

[0015] Preferably, the preparation method of the top coating is: 35-40 parts of styrene-acrylate emulsion, 15-20 parts of modified lignin, 2-3 parts of ethylene glycol butyl ether, 15-20 parts of improved self-healing microcapsules and 1-2 parts of polyacrylic acid dispersant are dispersed and mixed at a high speed of 1500 rpm for 30 minutes; ethyl acetate is added to adjust the viscosity to obtain the top coating.

[0016] Preferably, the preparation method of the modified lignin is as follows: dissolving 100 parts of lignin in a beaker containing 500 parts of N,N-dimethylformamide to obtain a lignin solution; adding 25-30 parts of succinic anhydride and 2 parts of triethylamine to the lignin solution, stirring the mixture in a water bath at 80°C for 5-6 hours to obtain a reaction solution; pouring the reaction solution into 200 parts of anhydrous ethanol, stirring the mixture evenly and allowing the mixture to settle, then filtering the precipitate, washing and drying the precipitate to obtain succinic anhydride-modified lignin; dispersing the succinic anhydride-modified lignin in 300 parts of anhydrous ethanol to obtain a suspension; adding 8-10 parts of silver nitrate to the suspension, stirring the mixture for 30 minutes, and then adding 20 parts of ascorbic acid; stirring the mixture at room temperature and avoiding light for 2-3 hours; allowing the mixture to settle after the reaction is completed, separating, washing and drying the precipitate to obtain the modified lignin.

[0017] Preferably, the preparation method of the improved self-repairing microcapsule is as follows: 20-25 parts of 2-naphthalene disulfide, 6-8 parts of modified benzalkonium chloride, and 60 parts of cyclohexane are mixed and stirred and dispersed at 40°C to obtain a microcapsule core material; then the microcapsule core material is poured into a polyvinyl alcohol aqueous solution, and shear emulsified at 1500rpm for 30min to obtain a mixed emulsion, and 5 parts of toluene diisocyanate are added during the shear emulsification; the mixed emulsion is continued to be stirred and reacted at room temperature for 2-3h to obtain a reaction system; after the reaction is completed, 1.5 parts of ethylenediamine are added to the reaction system, and the stirring reaction is continued for 1h; after the reaction is completed, the reaction is allowed to stand for stratification, and the reaction product is obtained after centrifugal washing, and the reaction product is vacuum dried to obtain an improved self-repairing microcapsule; The preparation method of modified benzalkonium chloride is as follows: 10 parts of benzalkonium chloride are dissolved in 50 parts of deionized water to prepare a benzalkonium chloride aqueous solution; 3.5 parts of sodium tetraphenylborate are added to 50 parts of deionized water to prepare a sodium tetraphenylborate aqueous solution; the sodium tetraphenylborate aqueous solution is poured into the benzalkonium chloride aqueous solution, the mixed solution is continuously stirred for 30 minutes, and the mixture is allowed to stand for precipitation for 1 hour after the stirring is stopped; after the precipitation is completed, the precipitate is washed and dried to obtain the modified benzalkonium chloride.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. In the present invention, on the one hand, the modified epoxy novolac resin enhances the bonding force with the metal substrate by chemical bonding and physical adsorption, and the modified introduced phosphate group can react chemically with the metal oxide on the metal surface to form a stable metal-oxygen-phosphorus bond, firmly anchoring the primer layer on the metal surface, greatly improving the coating adhesion. In terms of physical adsorption, the phenolic hydroxyl group in the molecular structure of epoxy novolac resin forms a hydrogen bond with the oxygen atom on the surface of the metal oxide, synergistically enhancing the physical adhesion. On the other hand, the modified epoxy novolac resin works in coordination with the interface treatment agent KH-550, and the silane group of KH-550 forms a siloxane bond passivation metal surface with the metal surface, and the amino group and the epoxy group remaining in the modified epoxy novolac resin form a CN bond and a CO bond by ring-opening addition, while the phenolic hydroxyl group, the phosphate group and the amino group and the silanol group of KH-550 form rich hydrogen bonds, and through multiple bonding, the bonding strength of the coating and the metal substrate is maximized.

[0019] 2. In the present invention, the modified carboxymethyl chitosan molecular chain contains a large number of hydroxyl and carboxymethyl functional groups, which can react with the epoxy groups in the phenolic epoxy resin during the curing process. This cross-linking reaction chemically bonds the modified carboxymethyl chitosan molecular chain to the phenolic epoxy resin network to form an interpenetrating polymer network. At the same time, when the coating is damaged, the modified carboxymethyl chitosan itself also has a certain antibacterial activity and can exert its antibacterial effect.

[0020] 3. In the present invention, modified lignin is added to the top coating. On the one hand, the modified lignin is uniformly dispersed in the styrene-acrylate emulsion film-forming matrix under the action of a dispersant, and the carboxyl group introduced into the lignin forms an ester bond with the matrix, which helps to anchor the modified lignin more firmly in the emulsion matrix, effectively enhance the binding force between the modified lignin and the styrene-acrylate emulsion matrix, and improve the interlayer adhesion, mechanical strength and other properties of the coating; on the other hand, although nanosilver has excellent antibacterial properties, nanosilver itself is also easily oxidized, resulting in reduced or even lost antibacterial activity; the physical isolation of the modified lignin matrix and the chemical stabilization of the phenolic hydroxyl group in scavenging free radicals can effectively protect the nanosilver from oxidation, maintain the nanosilver particles in a metallic state for a long time, and ensure the durability and effectiveness of the nanosilver antibacterial properties.

[0021] 4. In the present invention, on the one hand, the 2-naphthalene disulfide in the improved self-repairing microcapsule contains a disulfide bond, which has the characteristics of reversible fracture and recombination under external stimulation. When the coating is microscopically damaged, resulting in the breakage of the disulfide bond, the active sulfur radicals or ion pairs generated by the break can undergo a dynamic exchange reaction with the surrounding disulfide bonds or other active groups to reform new disulfide bonds and connect the broken molecular chains, thereby achieving self-healing of cracks or scratches. On the other hand, the 2-naphthalene disulfide molecular structure in the improved self-repairing microcapsule contains a naphthalene ring structure, and the benzalkonium chloride molecule contains a benzene ring structure, which can interact with the benzene ring structure of the styrene unit in the styrene-acrylate emulsion molecule of the top coating layer by π-π interaction, so that the repair agent can be more evenly and stably dispersed in the coating, thereby improving the effectiveness and durability of the self-repairing function. At the same time, benzalkonium chloride is a quaternary ammonium cationic surfactant that can form a synergistic antibacterial effect with the silver loaded by the modified lignin in the top coating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a schematic diagram of the antibacterial rate of Escherichia coli of the present invention; Figure 2 It is a schematic diagram of the antibacterial rate of Staphylococcus aureus of the present invention. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] See also Figure 1 to Figure 2 The present invention provides a rapid self-repairing antibacterial compression garbage truck metal plate coating and a preparation method thereof, and the technical scheme is as follows: Example 1 (I) Preparation of modified phenolic epoxy resin When preparing phosphorus-modified bisphenol A novolac epoxy resin, first accurately weigh 15 parts of monobutyl phosphate, place it in a vacuum drying oven at 60°C and vacuum degree -0.08MPa for vacuum dehydration and drying for 2 hours to complete the pretreatment of monobutyl phosphate; then, add 100 parts of bisphenol A novolac epoxy resin and 15 parts of pretreated monobutyl phosphate into a three-necked flask equipped with an electric stirrer, a thermometer and a condensation reflux device, then add 50 parts of ethyl acetate as a solvent, accurately weigh 0.3 parts of triethylamine as a catalyst and add it to the three-necked flask, and continuously pass nitrogen protection to the three-necked flask from the beginning to the end of the reaction to complete the preparation of the modification reaction; then put the three-necked flask in a heating mantle, set the temperature to 90°C, Start the electric stirrer, set the speed to 200 rpm, and stir the reaction at a constant temperature for 2 hours. During this period, samples can be taken regularly to measure the epoxy value or phosphorus content to monitor the reaction progress and carry out the modification reaction; after the reaction is completed, stop heating, remove the heating jacket, pass cooling water into the condensation reflux device, and cool the reaction system to room temperature; then add 2 parts of activated carbon to the cooled reaction solution, stir at room temperature for 30 minutes for adsorption and decolorization; then filter the reaction solution with a Buchner funnel and filter paper to remove the activated carbon and a small amount of insoluble matter to obtain a filtrate; finally, transfer the filtrate to a rotary evaporator, and perform vacuum distillation at a vacuum degree of -0.09 MPa and a water bath temperature of 60°C until no solvent is distilled out to obtain a modified phenolic epoxy resin.

[0025] (II) Preparation of modified carboxymethyl chitosan When preparing carboxymethyl chitosan modified by quaternary ammonium salt silane coupling agent, firstly, 0.5 parts of sodium hydroxide are dissolved in 400 parts of anhydrous ethanol to prepare a sodium hydroxide ethanol solution with a mass fraction of 0.125%, and after the preparation is completed, it is placed in a sealed container for standby use; then, under stirring, 100 parts of carboxymethyl chitosan powder are slowly added to the prepared sodium hydroxide ethanol solution, and stirring is continued for 30 minutes to ensure that the carboxymethyl chitosan is evenly dispersed in the solution to form a uniform carboxymethyl chitosan dispersion; then, under continuous stirring, 20 parts of 50% 2,3-epoxypropyltrimethylolpropane are added to the solution, and the mixture is stirred for 30 minutes. Ammonium chloride is slowly added dropwise to the carboxymethyl chitosan dispersion, and the dropping speed is strictly controlled to avoid excessive local concentration. After the addition is completed, the reaction device is placed in a 60°C water bath and the reaction is continued to be stirred for 4 hours to ensure that the quaternary ammonium salt modification reaction is fully carried out; after the reaction is completed, the modified product is centrifuged at a speed of 8000 revolutions per minute using a centrifuge, and the precipitate is washed three times with anhydrous ethanol to remove unreacted glycidyl trimethylammonium chloride and by-products, and centrifugation is performed after each washing; finally, the washed precipitate is placed in a vacuum drying oven at 60°C and dried for 24 hours to obtain modified carboxymethyl chitosan.

[0026] (III) Preparation of modified lignin 100 parts of organic solvent-based lignin with a particle size of 200 mesh were added to a beaker containing 500 parts of N,N-dimethylformamide, and stirred at room temperature until completely dissolved to prepare a lignin solution; then 25 parts of succinic anhydride were slowly added to the lignin solution, 2 parts of triethylamine were added dropwise as a catalyst, and the reaction was stirred in an 80°C water bath for 5 hours, and the temperature was monitored with a thermometer during the reaction; after the reaction was completed, it was cooled to room temperature, and the reaction solution was poured into 200 parts of anhydrous ethanol, stirred evenly, and then allowed to stand and precipitate, and then the precipitate was separated by suction, washed several times with a small amount of anhydrous ethanol, and then the washed precipitate was transferred to a vacuum drying oven and dried at 60°C under vacuum conditions for 24 hours to obtain succinic anhydride-modified lignin. 100 parts of succinic anhydride modified lignin are placed in a beaker containing 300 parts of anhydrous ethanol, and stirred at room temperature to form a uniform suspension; under stirring, 8 parts of silver nitrate are slowly added, stirred for about 30 minutes until completely dissolved, and then 17 parts of ascorbic acid are slowly added as a reducing agent; then the reaction is stirred for 2 hours at room temperature and protected from light, and the temperature is monitored with a thermometer, and a water bath is appropriately heated when necessary; after the reaction is completed, the precipitation is allowed to stand, and the upper clear liquid is separated by pouring, centrifugation or suction filtration, and the precipitate is washed with a small amount of anhydrous ethanol; finally, the washed silver-loaded succinic anhydride modified lignin is transferred to a vacuum drying oven, and vacuum dried at 60°C for more than 24 hours to obtain modified lignin.

[0027] 4. Preparation of improved self-healing microcapsules Dissolve 10 parts of benzalkonium chloride in 50 parts of deionized water to prepare a benzalkonium chloride aqueous solution, and add 3.5 parts of sodium tetraphenylborate to 50 parts of deionized water to prepare a sodium tetraphenylborate aqueous solution; after the two solutions are completely dissolved, slowly and uniformly pour the sodium tetraphenylborate aqueous solution into the benzalkonium chloride aqueous solution, and continue to stir during pouring. A white precipitate will precipitate immediately after mixing. Continue to stir the mixed solution at room temperature for 30 minutes, stop stirring, and let it stand for 1 hour to allow the precipitate to fully settle; after the precipitate is completely settled, carefully pour out the upper clear liquid and retain the bottom clear liquid. The mixture was stirred for 30 minutes, and then the upper washing liquid was removed by pouring out, and the washing step was repeated three times to remove the by-product sodium chloride and unreacted raw materials; after the last washing, the washing liquid was carefully removed, 20 parts of anhydrous ethanol was added to the precipitate for further washing and replacement of water, and the precipitate was collected by suction with a Buchner funnel after stirring and mixing. The filter cake was transferred to a vacuum drying oven and dried under vacuum conditions at 40°C for 24 hours to obtain modified benzalkonium chloride.

[0028] 2 parts of polyvinyl alcohol powder with a molecular weight of 8800 were added to 98 parts of deionized water, heated and stirred in a 70°C water bath until completely dissolved to prepare a 2% polyvinyl alcohol aqueous solution, cooled to room temperature for use; then, in an oil phase preparation container, 20 parts of 2-naphthalene disulfide and 6 parts of modified benzalkonium chloride were accurately weighed, 60 parts of cyclohexane were added, and placed on a magnetic stirrer, the speed was increased and heated to 40°C, and stirred until completely dissolved and evenly dispersed, which was used as the core material of the microcapsule; then, the oil phase dispersion was slowly poured into the prepared polyvinyl alcohol aqueous solution, and high-speed shearing and emulsification was performed at a speed of 1500rpm for 30 minutes using a high-speed disperser to form an oil-in-water emulsion; while the emulsion was stirred at high speed, a constant pressure dropping funnel was used to drip the emulsion. Slowly add 5 parts of toluene diisocyanate, control the dripping rate, maintain room temperature, and continue to stir the reaction at room temperature for 2 hours after the addition is completed, so that toluene diisocyanate and ethylenediamine polymerize at the oil-water interface to form a polyurea microcapsule wall; after the reaction is completed, add 1.5 parts of ethylenediamine to the system, and continue to stir the reaction for 1 hour to increase the degree of cross-linking; after the reaction is completed, let it stand to separate, pour off the upper aqueous phase liquid, wash the microcapsule precipitate with deionized water for 3 times, and after each washing, centrifuge it at a speed of 5000 rpm for 5 minutes to remove the washing liquid; finally, transfer the washed precipitate to a vacuum freeze dryer, freeze-dry it at a cold trap temperature of -50°C and a vacuum degree of 10Pa for 24 hours until the water is completely removed to obtain improved self-healing microcapsules.

[0029] (V) Coating Preparation of interface treatment layer: Weigh 5 parts of silane coupling agent KH-550 and add 95 parts of anhydrous ethanol, stir until completely dissolved to make a 5wt% solution. Use brushing, spraying or dipping to evenly apply it on the surface of the pretreated metal plate to form a thin layer, and dry it naturally at room temperature for 30 minutes.

[0030] Preparation of base coating: Accurately weigh 45 parts of modified phenolic epoxy resin, 20 parts of polyamide curing agent, 10 parts of modified carboxymethyl chitosan, 6 parts of zinc phosphate and 1 part of nano-silicon dioxide, and add them to a high-speed disperser. Start the high-speed disperser, set the speed to 1500rpm, and perform high-speed dispersion mixing for 30 minutes. In the later stage of dispersion, according to the actual viscosity of the coating, gradually add an appropriate amount of xylene solvent, continue stirring, and use a Tu-4 cup viscometer to measure the viscosity of the coating from time to time. When the viscosity of the coating is adjusted to 25 seconds, stop adding xylene solvent. After the above operations, a uniform and delicate modified carboxymethyl chitosan rapid self-repairing antibacterial and anticorrosive base coating can be obtained.

[0031] Primer coating: Pour the primer into the spray gun tank, adjust the spray pressure and spray width, and control the primer coating thickness to 30 to 50 microns. Use a vertical and uniform spraying method to evenly spray on the surface of the metal plate coated with the interface treatment agent. When spraying, pay attention to avoid defects such as uneven coating and sagging. After the primer coating is sprayed, let it stand for 5 minutes to allow it to level naturally, eliminate surface defects such as orange peel and brush marks generated during the spraying process, and improve the appearance quality of the coating.

[0032] Base coating curing: Place the leveled metal plate horizontally in a ventilated, cool, dry and clean environment, and cure it naturally at room temperature of about 25°C for 24 hours. During the curing process, avoid direct sunlight to prevent ultraviolet radiation from affecting the performance of the coating; at the same time, avoid pollution such as dust and particulate matter to keep the coating surface clean.

[0033] Preparation method of top coating: 35 parts of styrene-acrylate emulsion, 15 parts of modified lignin, 2 parts of ethylene glycol butyl ether, 15 parts of improved self-healing microcapsules and 1 part of polyacrylic acid dispersant are put into the dispersion tank of a high-speed disperser, and the high-speed disperser is started, the speed is set to 1500rpm, and the high-speed dispersion mixing is performed for 30 minutes to allow each component to be fully mixed in the styrene-acrylate emulsion. In the later stage of dispersion, the viscosity of the coating is measured with a Tu-4 cup viscometer, and ethyl acetate solvent is gradually added in an appropriate amount and stirred. When the viscosity of the coating is adjusted to 25 seconds, the addition of ethyl acetate is stopped to obtain the top coating coating.

[0034] Topcoat coating: Pour the prepared topcoat paint into the spray gun tank, adjust the spraying pressure, spray width and other parameters, so that the spraying thickness of the topcoat is also controlled at 30 microns to 50 microns. Use the same vertical and uniform spraying method as the base coat to evenly spray the topcoat on the surface of the cured base coat, and also pay attention to avoid defects such as uneven coating and sagging during the spraying process. After the topcoat is sprayed, let it stand for 5 minutes to allow it to level naturally.

[0035] Surface coating curing: Place the leveled metal plate horizontally in a ventilated, cool, dry and clean environment, and cure it at 65°C for 1.5 hours to obtain a fast self-repairing antibacterial compressed garbage truck metal plate coating.

[0036] Example 2 is different from Example 1 in that, in the preparation process of the modified phenolic resin, the amount of monobutyl phosphate used is 20 parts, the constant temperature stirring reaction time after adding triethylamine is 2 hours, and the other parameters and conditions are the same.

[0037] Example 3 is different from Example 1 in that, in the preparation process of the modified phenolic resin, the amount of monobutyl phosphate used is 20 parts, the constant temperature stirring reaction time after adding triethylamine is 2.5 hours, and the other parameters and conditions are the same.

[0038] Example 4 is different from Example 1 in that, in the preparation process of the modified phenolic resin, the amount of monobutyl phosphate used is 20 parts, the constant temperature stirring reaction time after adding triethylamine is 3 hours, and the other parameters and conditions are the same.

[0039] Example 5 is different from Example 3 in that, in the preparation process of modified carboxymethyl chitosan, the amount of trimethyl 2,3-epoxypropyltrimethylammonium chloride solution is 22.5 parts, and the reaction is stirred in a water bath at 60° C. for 5 hours; In the preparation process of modified lignin, the amount of succinic anhydride was 27.5 parts, and the reaction was stirred in a water bath at 80°C for 5.5 hours. The amount of silver nitrate was 9 parts, and the stirring reaction time after adding silver nitrate was 2.5 hours. During the preparation of the improved self-healing microcapsules, 2-naphthalene disulfide was added in an amount of 22.5 parts, benzalkonium chloride was added in an amount of 7 parts, and the reaction time of the mixed emulsion at room temperature was 2.5 h.

[0040] Example 6 is different from Example 3 in that, in the preparation process of modified carboxymethyl chitosan, the amount of trimethyl 2,3-epoxypropyltrimethylammonium chloride solution is 25 parts, and the reaction is stirred in a water bath at 60° C. for 6 hours; In the preparation process of modified lignin, succinic anhydride was used in an amount of 30 parts, and the reaction was stirred in a water bath at 80°C for 6 hours. Silver nitrate was used in an amount of 10 parts, and the stirring reaction time after adding silver nitrate was 3 hours. During the preparation of the improved self-healing microcapsules, 2-naphthalene disulfide was added in an amount of 25 parts, benzalkonium chloride was added in an amount of 8 parts, and the reaction time of the mixed emulsion at room temperature was 3 h.

[0041] Example 7 is different from Example 5 in that the amounts of the primer components are different: 47.5 parts of modified phenolic epoxy resin, 22.5 parts of polyamide curing agent, 12.5 parts of modified carboxymethyl chitosan, 7 parts of zinc phosphate, and 1.5 parts of nano-silicon dioxide; The dosage of the top coating components is different: 95 parts of styrene-acrylate emulsion, 12.5 parts of modified lignin, 2.5 parts of ethylene glycol butyl ether, 12.5 parts of improved self-healing microcapsules, and 1.5 parts of polyacrylic acid dispersant.

[0042] Example 8 is different from Example 5 in that the amounts of the primer components are different: 50 parts of modified phenolic epoxy resin, 25 parts of polyamide curing agent, 15 parts of modified carboxymethyl chitosan, 8 parts of zinc phosphate, and 2 parts of nano-silicon dioxide; The dosage of the top coating components is different: 100 parts of styrene-acrylate emulsion, 15 parts of modified lignin, 3 parts of ethylene glycol butyl ether, 15 parts of improved self-healing microcapsules, and 2 parts of polyacrylic acid dispersant.

[0043] Example 9 is different from Example 5 in that the amounts of the primer components are different: 47.5 parts of modified phenolic epoxy resin, 22.5 parts of polyamide curing agent, 12.5 parts of modified carboxymethyl chitosan, 7 parts of zinc phosphate, and 1.5 parts of nano-silicon dioxide; The dosage of the top coating components is different: 100 parts of styrene-acrylate emulsion, 15 parts of modified lignin, 3 parts of ethylene glycol butyl ether, 15 parts of improved self-repairing microcapsules, and 1-2 parts of polyacrylic acid dispersant.

[0044] Example 10 The amounts of the primer components are different: 50 parts of modified phenolic epoxy resin, 25 parts of polyamide curing agent, 15 parts of modified carboxymethyl chitosan, 8 parts of zinc phosphate, and 2 parts of nano-silicon dioxide; The dosage of the top coating components is different: 95 parts of styrene-acrylate emulsion, 12.5 parts of modified lignin, 2.5 parts of ethylene glycol butyl ether, 12.5 parts of improved self-healing microcapsules, and 1.5 parts of polyacrylic acid dispersant.

[0045] Comparative Example 1 is different from Example 1 in that unmodified bisphenol A novolac epoxy resin is used to prepare the primer coating, and other parameters and conditions remain unchanged.

[0046] Comparative Example 2 is different from Example 1 in that no interface treatment agent is used before coating the primer layer, and other parameters and conditions remain unchanged.

[0047] Comparative Example 3 is different from Example 1 in that unmodified carboxymethyl chitosan is used to prepare the primer, and other parameters and conditions remain unchanged.

[0048] Comparative Example 4 is different from Example 1 in that unmodified lignin is used to prepare the surface coating, and other parameters and conditions remain unchanged.

[0049] Comparative Example 5 is different from Example 1 in that only succinic anhydride is used to modify lignin, and silver nitrate is no longer used to load silver ions, and other parameters and conditions remain unchanged.

[0050] Comparative Example 6 is different from Example 1 in that only lignin is used to load silver ions, and succinic anhydride is not used to modify the lignin. Other parameters and conditions are the same.

[0051] Comparative Example 7 is different from Example 1 in that sulfite lignin is used as lignin, and other parameters and conditions are the same.

[0052] Comparative Example 8 is different from Example 1 in that benzalkonium chloride is not added during the preparation of the improved self-repairing microcapsules, and the other parameters and conditions are the same.

[0053] Comparative Example 9 is different from Example 1 in that, in the preparation process of the improved self-repairing microcapsules, benzalkonium chloride is used without modification, and the other parameters and conditions are the same.

[0054] Comparative Example 10 is different from Example 1 in that, in the preparation process of the improved self-healing microcapsules, di-n-butyl disulfide is used instead of 2-naphthalene disulfide, and the other parameters and conditions are the same.

[0055] Comparative Example 11 is different from Example 1 in that, during the preparation of the top coating, no improved self-repairing microcapsules are added, and the other parameters and conditions are the same.

[0056] Comparative Example 12 is different from Example 1 in that, in the preparation process of the top coating, n-butyl acrylate emulsion without a benzene ring structure is used instead of styrene-acrylate emulsion, and the other parameters and conditions are the same.

[0057] The difference between Comparative Example 13 and Example 1 is that during the curing process of the top coating, the curing temperature is 40 degrees, and the other parameters and conditions remain unchanged.

[0058] Test Example 1 Test object: Adhesion and hardness tests were conducted on the metal plate coatings prepared in Examples 1-4, Comparative Examples 1-2 and Comparative Example 4, and steel plates were used as the test plate material.

[0059] Test method: Adhesion test refers to GB / T9286-1998 "Scratch test for paint and varnish film", using 2mm, 6×6 scratching; hardness test refers to GB / T6739-2006 "Determination of paint film hardness by pencil method for paint and varnish", using pencil hardness method.

[0060] Table 1 Adhesion and hardness test results

[0061] In comparative example 1, the lack of monobutyl phosphate modification causes the modified phenolic epoxy resin to be unable to effectively utilize the dual mechanisms of chemical bonding and physical adsorption to form a strong bond with the metal substrate, superimposing the inherent defects of the resin body, resulting in decreased adhesion and hardness. In comparative example 2, no interface treatment agent was used, resulting in a lack of a covalent bond bridge formed by the silane coupling agent KH-550 between the coating and the metal substrate, and the interface bonding force was reduced from chemical bonding force to physical forces such as van der Waals force, and the microscopic interface bonding layer became weaker and the adhesion became worse; the decrease in interface bonding force caused the overall mechanical properties of the coating to decrease and the hardness to decrease. In comparative example 4, unmodified lignin was used. In combination with Example 1, the succinamide group introduced by the modified lignin formed a hydrogen bond with the C=O in the ester group of the styrene-acrylate emulsion, which enhanced the compatibility of lignin with the emulsion matrix, and at the same time, the lignin benzene ring structure formed a π-π conjugation with 2-naphthalene disulfide to enhance the interface bonding force. Unmodified lignin lacks the above-mentioned chemical modification effect, resulting in a weakening of the microscopic bonding force at the interface between the topcoat and the basecoat.

[0062] Test Example 2 Test object: The antibacterial property and antibacterial durability of the metal plate coatings prepared in Example 1, Examples 5-10 and Comparative Examples 3-9 were tested, and steel plates were used as the test plate material.

[0063] Test method: The antibacterial performance test refers to GB / T-218662008 standard, using Escherichia coli and Staphylococcus aureus as test strains, and the concentration is 5×10 5 cfu, in a sterile environment, drop 0.4mL-0.5mL of the test bacterial solution on the blank control template (A) and the antibacterial coating template (B). Incubate in a sterilized plate for 24 hours in a dark environment at 37°C and RH>90% relative humidity. Each sample was tested in parallel 3 times. Take out the sample that has been cultured for 24 hours, add 20mL of washing solution, rinse repeatedly, shake well, inoculate the washing solution into nutrient agar medium (NA), culture at 37°C for 24 hours, and count the live bacteria.

[0064] The antibacterial rate calculation formula is as follows: R=(AB) / A×100.

[0065] Wherein: R is the antibacterial rate of the test coating, expressed in (%); A is the number of colonies in the blank control group (cfu / piece); B is the number of colonies in the test coating (cfu / piece).

[0066] Antibacterial durability test: According to GB / T1771-91 "Determination of neutral salt spray resistance of paints and varnishes", the metal plate special layer is first subjected to salt spray treatment. The concentration of the NaCl solution used in the test is 50g / L, pH=6.8, and the treatment time is 480h; After salt spray treatment, accelerated aging test was carried out, xenon lamp treatment was used for 800 hours, and antibacterial performance test was carried out again.

[0067] Table 2 Antibacterial performance test results

[0068] In Comparative Example 3, the unmodified carboxymethyl chitosan imparts a certain initial antibacterial power to the base coating, which is derived from the electrostatic and hydrogen bonding between the amino and hydroxyl groups and the bacterial cell membrane, but its activity and compatibility with epoxy resin are not as good as those of the modified carboxymethyl chitosan, but the overall impact is small.

[0069] In comparative example 4, although the unmodified lignin topcoat has an initial antibacterial effect, it actually relies on the contribution of the modified carboxymethyl chitosan of the bottom coating and the organic antibacterial agent of the surface layer, and lacks the synergistic effect of silver ions and modified lignin; after aging, the poor compatibility leads to a loose coating structure, which accelerates the loss and degradation of the antibacterial components of the bottom coating, and the antibacterial rate is significantly reduced. In comparative example 5, only the succinic anhydride-modified lignin topcoat has good initial performance, but lacks the long-term antibacterial mechanism of silver ions. After aging, the antibacterial power mainly depends on modified carboxymethyl chitosan and benzalkonium chloride, and the antibacterial rate is significantly reduced, and the long-term effect is not good; the powdering of the coating also shows that the long-term stability of the structure is insufficient, indicating that silver ions are crucial to maintaining antibacterial persistence. In comparative example 6, only silver ions are loaded on lignin. Although silver ions provide effective initial antibacterial power, lignin is not modified by succinic anhydride, resulting in poor dispersibility, silver ions are easy to agglomerate and lose, and the antibacterial performance decays significantly after aging. In Comparative Example 7, although the sulfite lignin topcoat has a certain antibacterial synergistic effect, its sulfonic acid group enhances the water solubility, resulting in a decrease in the coating structure stability and interfacial bonding force; and in the aging process, there is no phenolic hydroxyl group to protect the silver ions, which accelerates the loss of antibacterial components and structural damage, and the antibacterial rate decreases significantly. Combining Comparative Examples 6 and 7, silver nanoparticles are highly dispersed in the matrix of succinic anhydride modified lignin to form a core-shell structure, with nanosilver as the core and modified lignin as the shell. The nanosilver particles will not undergo obvious agglomeration and maintain good dispersibility, which is attributed to the confinement and stabilization of the modified lignin. Lignin as a shell can well remove free radicals and prevent the nanosilver particles from being oxidized.

[0070] In Comparative Example 8, the microcapsules were not mixed with benzalkonium chloride, resulting in a complete lack of sustained-release antibacterial mechanism in the coating surface layer. The antibacterial power completely relied on the modified carboxymethyl chitosan of the base coating and the contribution of silver ions in the surface modified lignin, resulting in weakened antibacterial ability. At the same time, the antibacterial property of the metal coating could not be guaranteed under long-term aging. In Comparative Example 9, the microcapsules used unmodified benzalkonium chloride, which had poor solubility and reduced encapsulation efficiency and sustained release. After aging, benzalkonium chloride was more likely to leak and lose in advance, the sustained-release mechanism failed, the concentration of benzalkonium chloride in the coating surface layer decreased, and the antibacterial rate decreased significantly before and after aging, indicating that benzalkonium chloride modification to improve solubility and stable sustained-release ability of microcapsules is crucial for long-term antibacterial.

[0071] Test Example 3 Test object: The metal plate coatings prepared in Example 1 and Comparative Examples 10-13 were tested, and the test plate material used was a steel plate.

[0072] Test method: Repair performance test: Use load 110g / cm 2 The coating was scratched 5 times with a fine copper brush, and the salt spray treatment method in Test Example 2 was used. The coating state was observed after 120 hours of treatment.

[0073] Table 3 Coating repair performance test table

[0074] In Comparative Example 10, after the repair agent was replaced by di-n-butyl disulfide, the lack of π-π conjugation at the microscopic level did not completely deprive the repair ability, but significantly reduced the intermolecular interaction between the repair agent and the wall material and the matrix, restricting the solubility, diffusivity and reaction rate of the microcapsule core material with the curing agent, resulting in reduced quality and efficiency of the polyurea repair material, which was limited by the reduced repair efficiency. In Comparative Example 11, the self-repairing microcapsules were missing at the microscopic level of the top coating, resulting in a lack of endogenous repair mechanism at the scratch damage, permanent defects in the coating on the microstructure, direct exposure of the metal substrate, and the defective area became a corrosion source under long-term corrosion. The lack of self-repair function had a great impact on the long-term protective performance of the coating. In Comparative Example 12, after the topcoat emulsion was replaced with n-butyl acrylate without benzene ring, the π-π conjugated force at the microscopic level completely disappeared, the intermolecular and interfacial interaction forces within the topcoat were significantly weakened, and the coating cohesion, interfacial bonding force and structural strength were comprehensively reduced. The macroscopic performance was that the coating was more easily damaged after scratching, and the corrosive medium was easy to cause interface blistering after salt spray aging, and the self-repairing effect was difficult to effectively exert due to the change in the microstructure of the coating. In Comparative Example 13, the low-temperature curing of the topcoat resulted in insufficient aggregation and fusion of the emulsion polymer particles at the microscopic level, a significant reduction in the crosslinking density of the molecular chain, and a significant decrease in the film quality. The coating microstructure showed defects such as looseness and porosity, insufficient strength, and weak cohesion. The macroscopic performance was that the coating was fragile and vulnerable after scratching, and the corrosive medium was fast and caused large-scale shedding after salt spray aging. Even if the microcapsules released the repair agent, it was difficult to make up for the microstructural defects of the coating, and the self-repairing performance was seriously impaired.

[0075] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A rapid self-repairing antibacterial compression garbage truck metal plate coating, characterized by: The rapid self-repairing antibacterial compressed garbage truck metal plate coating comprises a base coating and a top coating, wherein the base coating components comprise: 45-50 parts of modified phenolic epoxy resin, 20-25 parts of polyamide curing agent, 10-15 parts of modified carboxymethyl chitosan, 6-8 parts of zinc phosphate, and 1-2 parts of nano-silicon dioxide; The top coating component includes: 90-100 parts of styrene-acrylate emulsion, 10-15 parts of modified lignin, 2-3 parts of ethylene glycol butyl ether, 10-15 parts of improved self-repairing microcapsules, and 1-2 parts of polyacrylic acid dispersant; The modified phenolic epoxy resin raw materials include: bisphenol A phenolic epoxy resin and monobutyl phosphate; The modified carboxymethyl chitosan raw material comprises: carboxymethyl chitosan and 2,3-epoxypropyltrimethylammonium chloride; The improved self-repairing microcapsule raw materials include: 2-naphthalene disulfide, modified benzalkonium chloride, and polyvinyl alcohol; The modified lignin raw material comprises: lignin, succinic anhydride and silver nitrate.

2. The rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 1 is characterized by: The molecular weight of the polyvinyl alcohol is 88,000.

3. The rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 1 is characterized by: The modified lignin preparation raw materials include: The particle size of the lignin is 200 meshes, and the lignin is an organic solvent type lignin.

4. A method for preparing a rapid self-repairing antibacterial compressed garbage truck metal plate coating as claimed in any one of claims 1 to 3, characterized in that: The preparation method of the rapid self-repairing antibacterial compressed garbage truck metal plate coating is as follows: an interface treatment agent is applied to a metal plate, and the metal plate is naturally dried at room temperature for 30 minutes to obtain a pre-treated metal plate; a primer coating is sprayed on the surface of the pre-treated metal plate, and the metal plate is cured at 25°C for 24 hours to obtain a primer coating metal plate; the interface treatment agent is applied to the primer coating metal plate, and the metal plate is naturally dried at room temperature for 30 minutes to obtain a pre-treated primer coating metal plate; a top coating coating is sprayed on the surface of the pre-treated primer coating metal plate, and the metal plate is cured at 65°C for 1.5 hours to obtain a rapid self-repairing antibacterial compressed garbage truck metal plate coating; In parts by weight, the interface treatment agent is prepared by dissolving 5 parts of KH-550 in 95 parts of anhydrous ethanol.

5. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 4 is characterized in that: The preparation method of the primer coating is as follows: 45-50 parts of modified phenolic epoxy resin, 20-25 parts of polyamide curing agent, 10-15 parts of modified carboxymethyl chitosan, 6-8 parts of zinc phosphate and 1-2 parts of nano silicon dioxide are weighed, dispersed and mixed at a speed of 1500 rpm for 30 minutes, and xylene is added to adjust the viscosity to obtain the primer coating.

6. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 5 is characterized in that: The preparation method of the modified phenolic epoxy resin is as follows: in a three-necked flask, 100 parts of bisphenol A phenolic epoxy resin and 15-20 parts of monobutyl phosphate are added, 50 parts of ethyl acetate is added as a solvent, and then 0.3 parts of triethylamine is added, and the reaction is carried out at a speed of 200 rpm and 90° C. with constant temperature stirring for 2-3 hours, and then the reaction system is cooled to room temperature; 2 parts of activated carbon are added to the reaction system, and the reaction system is stirred at room temperature for 30 minutes for adsorption and decolorization, and a filtrate is obtained by filtering; and finally the filtrate is vacuum distilled to obtain the modified phenolic epoxy resin.

7. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 5, characterized in that: The preparation method of the modified carboxymethyl chitosan is as follows: under stirring, 100 parts of carboxymethyl chitosan powder is added to 400 parts of sodium hydroxide ethanol solution with a mass fraction of 0.125%, and stirred for 30 minutes to prepare a carboxymethyl chitosan dispersion; then 20-25 parts of 2,3-epoxypropyltrimethylammonium chloride solution with a mass concentration of 50% is added to the carboxymethyl chitosan dispersion, and the mixture is stirred in a water bath at 60° C. for reaction for 4-6 hours; after the reaction is completed, the precipitate is centrifuged and washed for 3 times; and finally the precipitate is dried in a vacuum drying oven to obtain the modified carboxymethyl chitosan.

8. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 4 is characterized in that: The preparation method of the top coating is as follows: 35-40 parts of styrene-acrylate emulsion, 15-20 parts of modified lignin, 2-3 parts of ethylene glycol butyl ether, 15-20 parts of improved self-repairing microcapsules and 1-2 parts of polyacrylic acid dispersant are dispersed and mixed at a high speed of 1500 rpm for 30 minutes; ethyl acetate is added to adjust the viscosity to obtain the top coating.

9. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 8, characterized in that: The preparation method of the modified lignin is as follows: 100 parts of lignin are added to 500 parts of N,N-dimethylformamide to obtain a lignin solution; 25-30 parts of succinic anhydride and 2 parts of triethylamine are added to the lignin solution, and the mixture is stirred in a water bath at 80°C for 5-6 hours to obtain a reaction solution; the reaction solution is poured into 200 parts of anhydrous ethanol, stirred evenly, and then allowed to stand for precipitation, and the precipitate is separated by suction filtration, washed, and dried to obtain succinic anhydride modified lignin; The succinic anhydride modified lignin is dispersed in 300 parts of anhydrous ethanol to obtain a suspension; 8-10 parts of silver nitrate are added to the suspension, stirred for 30 minutes, and then 20 parts of ascorbic acid are added; the reaction is stirred for 2-3 hours at room temperature and in the dark; after the reaction is completed, the precipitate is allowed to stand and precipitate is separated, washed, and dried to obtain the modified lignin.

10. The method for preparing the rapid self-repairing antibacterial compressed garbage truck metal plate coating according to claim 8, characterized in that: The preparation method of the improved self-repairing microcapsule is as follows: 20-25 parts of 2-naphthalene disulfide, 6-8 parts of modified benzalkonium chloride, and 60 parts of cyclohexane are mixed and stirred and dispersed at 40° C. to obtain a microcapsule core material; then the microcapsule core material is poured into a polyvinyl alcohol aqueous solution, sheared and emulsified at 1500 rpm for 30 minutes to obtain a mixed emulsion, and 5 parts of toluene diisocyanate are added during the shear emulsification; the mixed emulsion is continued to be stirred and reacted at room temperature for 2-3 hours to obtain a reaction system; after the reaction is completed, 1.5 parts of ethylenediamine are added to the reaction system, and the stirring reaction is continued for 1 hour; after the reaction is completed, the reaction system is allowed to stand for stratification, and a reaction product is obtained after centrifugal washing, and the reaction product is vacuum dried to obtain an improved self-repairing microcapsule; The preparation method of the modified benzalkonium chloride is as follows: 10 parts of benzalkonium chloride are dissolved in 50 parts of deionized water to prepare a benzalkonium chloride aqueous solution; 3.5 parts of sodium tetraphenylborate are added to 50 parts of deionized water to prepare a sodium tetraphenylborate aqueous solution; the sodium tetraphenylborate aqueous solution is poured into the benzalkonium chloride aqueous solution, the mixed solution is continuously stirred for 30 minutes, and the mixture is allowed to stand for precipitation for 1 hour after the stirring is stopped; after the precipitation is completed, the precipitate is washed and dried to obtain the modified benzalkonium chloride.

Citation Information

Cited By

  • Preparation method of filling and coating quick-drying type resin anti-corrosion paint

    CN120842945A